2019
DOI: 10.3151/jact.17.195
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Material Properties of a Thick Concrete Wall Exposed to Ordinary Environmental Conditions in a Nuclear Reactor Building: the Contribution of Cement Hydrates and Feldspar Interaction

Abstract: A variation of material properties with depth is observed in a massive, seismic-resistant internal wall of Unit 1 of the Hamaoka Nuclear Power Plant (NPP) 45 years after its construction. The maximum values are attained in the center of the structural element and gradually decrease towards the surface, while still well exceeding the required performance. It is found that this trend can be mostly attributed to the reaction between cement hydrates and rock-forming minerals of a feldspar group, which releases sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the latter, after 16½ years under a relative humidity higher than 80% and a highly soluble alkali concentration, the cement hydrates reacted with the silica and alumina released from feldspar group aggregates and formed Al‐tobermorite. In contrast to the general cases where the concrete strength decreases over time, the strength and Young's modulus of the concrete wall of the Hamaoka nuclear power plant increased due to this reaction 66 and Al‐tobermorite formation. Maruyama et al 65 .…”
Section: Introductionmentioning
confidence: 67%
“…In the latter, after 16½ years under a relative humidity higher than 80% and a highly soluble alkali concentration, the cement hydrates reacted with the silica and alumina released from feldspar group aggregates and formed Al‐tobermorite. In contrast to the general cases where the concrete strength decreases over time, the strength and Young's modulus of the concrete wall of the Hamaoka nuclear power plant increased due to this reaction 66 and Al‐tobermorite formation. Maruyama et al 65 .…”
Section: Introductionmentioning
confidence: 67%
“…To systematize the knowledge for long-term use, it is necessary to accumulate health monitoring data of actual structures, crack investigations, and detailed analysis of physical properties. For example, it has been reported that an additional reaction between hydrates and rock-forming minerals in thick concrete members contributed to a significant increase in strength [81,82]. This phenomenon cannot be observed in laboratory experiments.…”
Section: Discussionmentioning
confidence: 98%
“…The drying period took 93 days, ensuring a quasi-equilibrium condition [0.01%/day according to (Wu et al 2019)] for all samples. This 105°C was selected as the reference that is the most commonly used, and 20°C and 40% RH was selected since this drying state is similar to the drying condition on the surface of thick concrete walls in nuclear power plants [an estimation was made based on references (Rymeš et al 2019;Maruyama et al 2021)].…”
Section: Water Absorption Test Methodsmentioning
confidence: 99%
“…To assess the level of contamination in concrete structures accurately, it is important to consider water transport and microstructural changes within the material. The concrete in the Fukushima NPP buildings has a relatively low moisture content after many years of service (Rymeš et al 2019;Maruyama et al 2021). After the accident, part of the concrete surface was exposed to heat and drying conditions, then was subsequently exposed to seawater and contaminated water.…”
Section: Introductionmentioning
confidence: 99%